Association between oxidative balance score and allergic rhinitis in American adults: a cross-sectional study - Tian, Yanhua; Sun, Wenbo; Song, Jijun (Frontiers in Nutrition, 2025)
BackgroundOxidative stress has been implicated in the development of allergic rhinitis (AR), yet its population-level impact using composite oxidative metrics remains underexplored. This study aimed to investigate the association between the oxidative balance score (OBS), a composite indicator of pro- and antioxidant exposures, and AR in U.S. adults.MethodsWe analyzed data in the 2005–2006 NHANES. An OBS, comprising 16 dietary and 4 lifestyle factors, was calculated and analyzed as both a continuous variable and by quartiles. Associations with AR were assessed using multivariable logistic regression and restricted cubic spline (RCS) models. Survey-weighted analyses were additionally performed to account for the complex sampling design and assess national representativeness. Sensitivity analyses included dietary energy adjustment (residual method), exclusion of asthma or supplement users, and alternative AR definitions. Exploratory subgroup analyses were further conducted across demographic and clinical strata with false discovery rate (FDR) correction for multiple testing.ResultsAmong 1,491 adults, higher total and dietary OBS were significantly associated with AR. In fully adjusted models, each unit increase in total OBS corresponded to 2% higher odds of AR (OR = 1.02; 95% CI: 1.01–1.04), and each SD increase to 19% higher odds (OR = 1.19; 95% CI: 1.06–1.34). Dietary OBS showed a similar association (OR = 1.03; 95% CI: 1.01–1.04), whereas lifestyle OBS was not significant (OR = 1.01; 95% CI: 0.93–1.08). Quartile analyses revealed dose–response relationships, with Q4 of total (OR = 1.67; 95% CI: 1.20–2.33) and dietary OBS (OR = 1.60; 95% CI: 1.16–2.22) showing significantly increased odds compared with Q1. In survey-weighted analyses, total OBS remained significantly associated with AR, whereas dietary and lifestyle OBS were not. These associations remained robust in sensitivity analyses.ConclusionIn a nationally representative sample, higher OBS was associated with greater odds of AR after adjustment, with an approximately linear association. Associations were stronger for dietary than lifestyle OBS, and the positive association persisted for total OBS in survey-weighted models. Overall, these findings suggest OBS may serve as a practical composite marker of diet-related redox balance in AR epidemiology.